Hubungan Pemaafan dan Resiliensi pada Remaja Penyintas Perceraian Orang Tua - Annisa, Annisa; Sari, Novita; Sari, Kartika; Dahlia, Dahlia (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2025)
Divorce is widely viewed as a means of resolving marital conflict; however, it has the potential to negatively affect adolescents. For adolescents, parental divorce is one of the most stressful life events, often associated with long-term emotional and behavioral problems. As a result of their parents' divorce, adolescents feel depressed and struggle to cope with lifes challenges into adulthood. Forgiveness is proven to mitigate the negative impact of parental divorce, enabling adolescents to adapt and bounce back and preparing them to face future challenges both physically and psychologically. This research aims to determine the relationship between forgiveness and resilience in 104 adolescent survivors of parental divorce in Aceh, using quota sampling and participated in completing the Brief Resilience Scale (BRS) and Transgression-Related Interpersonal Motivations (TRIM-18). The data analysis shows a significance value (p) =0.001 and a correlation coefficient (r) = -0.631, indicates significant positive correlation between forgiveness and resilience. This implies that the higher the level of forgiveness, the higher the level of resilience, and conversely, the lower the level of forgiveness, the lower the level of resilience. This research found that these adolescent have high levels of both forgiveness and resilience.Perceraian umumnya dianggap sebagai resolusi konflik interpersonal dalam pernikahan, tetapi fenomena ini dapat berdampak negatif bagi remaja. Bagi remaja, perceraian orang tua adalah salah satu peristiwa kehidupan yang berpotensi menimbulkan stres dikaitkan dengan masalah emosional dan masalah perilaku jangka panjang. Akibat dari perceraian orang tua, remaja merasa tertekan dan kesulitan menghadapi tantangan hidup hingga dewasa. Resiliensi dan pemaafan terbukti dapat mengurangi dampak negatif yang ditimbulkan dari perceraian orang tua sehingga remaja mampu beradaptasi dan bangkit kembali dan remaja siap secara fisik dan psikologis untuk menghadapi tantangan di masa depan. Penelitian ini bertujuan untuk mengetahui hubungan pemaafan dengan resiliensi pada 104 remaja penyintas perceraian orang tua di Aceh yang dipilih menggunakan teknik quota sampling dan berpartisipasi dalam pengisian instrumen Brief Resilience Scale (BRS) dan Transgression-Related Interpersonal Motivations (TRIM-18). Analisis data menunjukkan nilai signifikansi (p) =0.001 dan nilai koefisien korelasi (r) = -0.631, artinya terdapat hubungan positif signifikan antara pemaafan dengan resiliensi. Penelitian ini menemukan bahwa semakin tinggi pemaafan maka semakin tinggi resiliensi, begitu juga sebaliknya semakin rendah pemaafan maka semakin rendah resiliensi. Penelitian ini menemukan bahwa remaja penyintas perceraian orang tua memiliki pemaafan yang tinggi serta resiliensi yang tinggi.